Studying the effect of chemical solutions on diffusion coefficient of composite material reinforced with Kevlar-carbon fibres. (Journal of the College of Basic Education, 2023)
In this research the effect of immersion in chemical solutions have been studied including acids ,alkalise ,salts .three groups of specimens have been prepared .the first group have1layer of Kevlar-carbon fibres ,the second group have two layers of Kevlar-carbon fibres while the third group have three layers . the three groups of specimens have been immersed synchronizly in acids(HNO3),Alkalise (NaOH), salt (NaCL) results showed remarkable effect of NaOH solution in comparison with HNO3 solution .for NaCL solution pure PE showed fluctuation in weight gain and less absorption than the reinforced composites .reinforcing with 3layers of carbon-kevlar fibres showed good stability against acids while 2 layer reinforcing showed better stability for NaOH solution.